Comprehensive Identification of Principal Lipid Classes and Tocochromanols in Silkworm (Antheraea pernyi and Bombyx mori) Pupae Oils. Issue 2 (11th December 2019) - Wang, Weifei; Xu, Long; Zou, Yuxiao; Pang, Daorui; Shi, Wei; Mu, Lixia; Li, Erna; Lan, Dongming; Wang, Yonghua; Liao, Sentai
Abstract: A comprehensive identification of lipid compositions and tocochromanols in Antheraea perny i ( A. perny i) and Bombyx mori ( B. mori ) pupae oil is reported in the present study. Fatty acid profiling shows that both oils contain high levels (79.67% vs 71.11%) of unsaturated fatty acids, especially linoleic acid and linolenic acid. Moreover, linolenic acid is preferentially enriched at the sn ‐2 positions of triacylglycerols (TAGs). Liquid chromatograph‐mass spectrometry (LC‐MS) analysis demonstrates that POO (TAG with one palmitoyl and two oleoyls) is the primary TAG form with percentages of 20.18% in A. perny i and 15.00% in B. mori . The dominating phospholipid species are phosphatidylcholine (PC, 30.40% vs 54.61%) and phosphatidylethanolamine (PE, 34.82% vs 20.39%). Four sterol constituents with total contents of 382.56 ± 3.12 and 371.65 ± 2.98 µg g −1 are identified and analyzed quantitatively. Additionally, the levels of tocochromanols (20.15 ± 0.89 vs 17.15 ± 0.71 mg g −1 ) are quantified in both silkworm pupae oils. Overall, silkworm oil acts as an enriched source of functional lipids and tocochromanols. Practical Applications : A systematic investigation on the principal lipid classes and tocochromanols of Antheraea perny i pupae and Bombyx mori pupae oil is reported in this study. The informative data provide supporting evidence for comprehensive utilization of silkworm oil for production of nutritional and healthy products. Abstract : Silkworm pupae is widely consumed in some Asian countries. The lipid compositions of non‐mulberry Antheraea pernyi pupae and mulberry Bombyx mori pupae oil are reported comprehensively in this study, including fatty acids, triacylglycerols, phospholipids, and sterols. Additionally, tocochromanols, are analyzed quantitatively. The high levels of linolenic acid enable silkworm pupae oil to be a good source of functional lipids.